FORMULATION AND EVALUATION OF SACHA INCHI OIL-BASED SERUM AS AN ANTI-AGING COSMETIC - Elianasari, Elianasari (Indonesian Journal of Cosmetics, 2025)
Skin aging is a complex biological process influenced by intrinsic factors (genetic, hormonal, and metabolic) and extrinsic factors (UV exposure, pollution, and lifestyle), characterized by decreased collagen and elastin production and increased oxidative stress. Sacha Inchi seed oil is known for its high content of polyunsaturated fatty acids and bioactive compounds such as tocopherols and phenolics, which exhibit antioxidant activity beneficial to skin health. This study aimed to formulate and evaluate the physical stability of a facial serum containing Sacha Inchi seed oil (Plukenetia volubilis L.) as a natural anti-aging agent. The formulation was assessed through physical quality tests, including organoleptic properties, homogeneity, spreadability, viscosity, pH, and a cycling stability test over six cycles at 4°C and 40°C to simulate extreme storage conditions. The results showed that the serum maintained its physical stability after the cycling test. No significant changes were observed in organoleptic properties (color, odor, texture), and the formulation remained homogeneous with no phase separation. Viscosity slightly decreased from 3920 to 3643 mPa·s, while spreadability decreased from 13.6 to 9.4 g·cm/s, yet both remained within acceptable cosmetic limits. The pH remained stable between 5.44 and 5.47, aligning with the physiological skin pH range (4.5–6.5). These findings indicate that Sacha Inchi oil can be effectively formulated into a physically stable serum and holds promise for development as a natural active ingredient in anti-aging skincare products.